Soviet Social Insurance Model in Lithuania: Structure and Ideology - Guogis, Arvydas; Bogdanova, Natalija (Lithuanian Journal of Statistics, 2011)
This article analyses the structure and ideology of the Soviet social insurance system. In the whole territory of theUSSR the same principles and laws of social insurance were applied. However, in several Soviet republics, for example Lithuania,some specific elements were observed which influenced the administrative methods in social security, social insurance and socialsupport. The article explains the nature of social insurance expenditure. We define and explain the branches of social insurance in the USSR: old age and disability pensions, illness, maternity, funeral and unemployment benefits (the latter were paid in the early Sovietperiod only). The article deals with official USSR and Lithuanian SSR statistics, mainly from the last Soviet period (beginning 1975), when Soviet social insurance reached its limits and showed its potential. Although Soviet social insurance was related to theprinciples of the Bismarckian work record and former earnings, it was however financed from Moscow's centrally organised budgetand was not related to meaningful contributions of employers and employees. The one-party communist system had a big role in thefunctioning of social insurance in the USSR and the Lithuanian SSR.
Keywords: Soviet social security scheme; centralized budget of social insurance; Soviet pensions system